OS CONCEITOS DE CULTURA HISTÓRICA, CONSCIÊNCIA HISTÓRICA E APRENDIZAGEM HISTÓRICA: UM ESTUDO BIBLIOMÉTRICO - Carvalho Peçanha Guimarães, Tatiane; Castro Manhães, Fernanda; Tavares do Carmo, Gerson; Vasconcelos de Andrade, Lívia; Francisca Sant’Anna, Nadir (LINKSCIENCEPLACE, 2026)
Research in the field of Historical Education has sought to investigate the relationship of subjects with historical knowledge, understanding the cognitive processes involved in the perception and learning of concepts in history, defined by Lee (2001) as substantive concepts. Historical Education points to a learning in the teaching of history focused on the historical sense of the experience of time, that is, for structural changes in the historical consciousness, considering the historical culture of the students. As a relatively recent approach, mainly in Brazil, and its relevance to new investigations in the teaching of history, this study had as objective to collect data that reveal the number of publications of works on the theme historical culture, historical awareness and learning Historical, obtained in the Scopus database, between the years of 2012 to 2016. As methodology was carried out a simple search with the keywords historical culture + historical consciousness + historical learning, simultaneously. The results indicated from the Scopus database point to a reduced number of publications in the last 5 (five) years, indicating a field still little investigated, in Brazil, as in the world.